2022
DOI: 10.3390/ijerph192416750
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Occupational Stress and Mental Health among Chinese Soccer Referees in the Early Stage of Reopening Soccer Matches during the COVID-19 Pandemic Outbreak: A Moderated Mediation Model

Abstract: Background: The sudden and unpredictable changes caused by the COVID-19 pandemic are a serious threat to the occupational stress and mental health of referees worldwide, which has not attracted widespread attention. The mental health of football referees has a certain influence on their job satisfaction or the accuracy of judgments. Methods: This study constructed a moderated mediation model to explore the buffer factors between occupational stress and mental health in Chinese soccer referees in the early stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Our study supports previous research indicating a significant direct effect of job stress on various Chinese workers, including soccer referees (Liu et al, 2022), emergency physicians (Jiang et al, 2022;Tian et al, 2022), and healthcare workers (Ge et al, 2021). This aligns with the broader ERI literature, which consistently points out the negative impacts of imbalances between efforts and rewards on workrelated outcomes (Deng et al, 2021;Fei et al, 2023), demonstrating the ERI model's wide applicability across different occupational contexts in China.…”
Section: Discussionsupporting
confidence: 90%
“…Our study supports previous research indicating a significant direct effect of job stress on various Chinese workers, including soccer referees (Liu et al, 2022), emergency physicians (Jiang et al, 2022;Tian et al, 2022), and healthcare workers (Ge et al, 2021). This aligns with the broader ERI literature, which consistently points out the negative impacts of imbalances between efforts and rewards on workrelated outcomes (Deng et al, 2021;Fei et al, 2023), demonstrating the ERI model's wide applicability across different occupational contexts in China.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, some studies have suggested that the probability of suffering from mental illness may be reduced among athletes involved in team sports compared to those engaging in individual sports [ 4 , 8 ]. An increased sense of belonging and greater accessibility to social support could explain these differences [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For football referees, physical fitness and professional skills are the foundations of their career development. After being quarantined at home for a long time, they will worry about the decline of physical strength and the occupational pressure caused by poor professional skills in the early days of sports competitions [ 39 ]. A study of French athletes showed higher anxiety scores when they returned to competition after COVID-19 [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In short, the current studies on the impact of the COVID-19 lockdown on quality of life mostly focus on medical staff and students, and most of the studies in the sports industry also focus on athletes, with little research on football referees. To our knowledge, there are no more than 30 studies on the impact of the COVID-19 epidemic on football referees, and most of them focus on physical function, professional skills, and mental health, while there is only one piece of literature on Chinese football referees [ 39 ]. Therefore, based on the stressor theory model and the job demand-resource model, this paper explores the impact of the COVID-19 lockdown on the quality of life of Chinese football referees as well as the influencing mechanisms of occupational stress and job burnout.…”
Section: Introductionmentioning
confidence: 99%